The concept of participation of food industry enterprises in ensuring food security of the state - Klius, V. (Global Prosperity, 2023)
Klius V. The concept of participation of food industry enterprises in ensuring food security of the state. Global Prosperity. 2023. Vol. 3. Issue 1